Prevalence of antineutrophil cytoplasmic autoantibodies in patients with tuberculosis - Flores-Suárez, Luis Felipe; Cabiedes, J.; Villa, A. R.; Woude, Fokko J. van der; Alcocer-Varela, J. (Rheumatology, 2003)
OBJECTIVE: To determine the prevalence of antineutrophil cytoplasmic autoantibodies (ANCA) in sera of patients with tuberculosis compared with healthy control subjects and a group of patients with atopic asthma. METHODS: The presence of ANCA was examined in patients with tuberculosis, and in asthmatic patients and healthy subjects as control groups, by means of indirect immunofluorescence (IIF) and enzyme-linked immunosorbent assay (ELISA) to detect anti-proteinase 3 (PR3-ANCA) and antimyeloperoxidase (MPO-ANCA) antibodies. RESULTS: ANCA were present in 20 (44.4%) of 45 tuberculosis patients by IIF (16 c-ANCA, four p-ANCA) and in 18 (40%) patients by ELISA (15 PR3-ANCA, three MPO-ANCA). High odds ratios for ANCA positivity were observed for tuberculosis patients when compared with both control groups. ANCA results were not related to the category of tuberculosis, stage of disease, presence of concomitant diseases or pharmacotherapy. CONCLUSIONS: As many clinical similarities between tuberculosis and Wegener's granulomatosis exist, we propose that a positive ANCA test in patients living in countries with a high prevalence of tuberculosis must be carefully interpreted as indicative of systemic vasculitis, especially when no signs of extrapulmonary involvement occur.
Gesehen am 15.06.2022